2021
DOI: 10.1016/j.neuroimage.2021.117956
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-induced cerebral pulsatility, brain structure, and cognition in middle and older-aged adults

Abstract: Changes of cardiac-induced regional pulsatility can be associated with specific regions of brain volumetric changes, and these are related with cognitive alterations. Thus, mapping of cardiac pulsatility over the entire brain can be helpful to assess these relationships. A total of 108 subjects (age: 66.5 ± 8.4 years, 68 females, 52 healthy controls, 11 subjective cognitive decline, 17 impaired without complaints, 19 MCI and 9 AD) participated. The pulsatility map was obtained directly from resting-state funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…We note that the acquired multi‐TE BOLD data had a long TR compared to the more rapid acquisition times that are currently available. Undersampling the cardiac signal that is contained in the BOLD data leads to aliasing; nevertheless, the network was able to generate BOLD pulsatility maps with high image similarity to ground truth, in line with prior studies that have demonstrated extraction of cardiac‐related signals from long‐TR BOLD images 7,10,11 . We have assumed that the neural network trained on FFT input images contained subharmonic pulsatility features.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We note that the acquired multi‐TE BOLD data had a long TR compared to the more rapid acquisition times that are currently available. Undersampling the cardiac signal that is contained in the BOLD data leads to aliasing; nevertheless, the network was able to generate BOLD pulsatility maps with high image similarity to ground truth, in line with prior studies that have demonstrated extraction of cardiac‐related signals from long‐TR BOLD images 7,10,11 . We have assumed that the neural network trained on FFT input images contained subharmonic pulsatility features.…”
Section: Discussionsupporting
confidence: 74%
“…Using phase contrast MRI, it is possible to calculate time‐resolved blood flow velocities directly from perforating cerebral arteries 5,6 . BOLD MRI is a popular functional neuroimaging technique, which provides additional physiological contrast that includes autonomic, respiratory, and cardiac related signals 2,7–14 . Intracranial BOLD pulsatility reflects flow‐related blood volume changes and spin history inflow effects 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a clinical perspective, cardiac pulsatility has recently shown its application in the definition of pathophysiological biomarkers and monitoring of disease progression in age-related neurodegenerative disorders (Kim et al (2021)), which might benefit from WHOCARES implementation. Another example may be the case of stroke patients where, sometimes, the heart-rate shows pathologicalrelated modifications and changes in cardiac pulsatility (Geurts et al (2019)).…”
Section: Limitations and Future Workmentioning
confidence: 99%